Penggunaan Sistem Poin Partisipasi untuk Kemampuan Berbicara Siswa pada Siswa Kelas Delapan SMPN 8 Makassar - Dini Savonarola Manyanyi (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
ABSTRACT This research aimed at finding out the students’ speaking ability before and after using participation point system method in teaching speaking. The independent variable was using participation point system method and the dependent variable was students’ speaking achievement. The sample of the research were 36 students of class VIII6 at SMPN 8 Makassar in the second semester academic year 2021/2022. The design of this research was quantitative design and the method used in this research was pre-experimental one group pretest-posttest research.The result of the research showed that there was a difference between pre-test and post-test score of the students. Theaverage score of pre-test was 48,78 and the average score of post-test was 86,11. Based on the result can be seen that after the researcher gave treatment in post-test was higher than pre-test. Therefore, participation point system becomes an appropriate method in teaching speaking of class VIII6 at SMPN 8 Makassar. Key Words : Participation Point System, Speaking Ability